Faktor-Faktor Penentu Kesiapan Emiten LQ45 dalam Mengimplementasikan Standar Pengungkapan Keberlanjutan (IFRS S1/S2): Pengukuran Kuantitatif Readiness Score - Maurinawati Azizah; Adria Wuri Lastari; Marwan Setiawan (ARZUSIN, 2026)
Sustainability reporting based on IFRS S1 and IFRS S2 has become an important issue in improving the transparency of corporate sustainability information, but studies on the readiness of LQ45 issuers through quantitative measurement of readiness scores remain limited. This study aims to analyze the effects of company size, profitability, and leverage on the readiness of LQ45 issuers to implement the IFRS S1/S2 sustainability disclosure standards. This study employed a quantitative approach with descriptive and explanatory designs. The research sample consisted of 30 LQ45 issuers selected using the purposive sampling technique. Data were collected through documentation of annual reports and sustainability reports for 2024 and were then analyzed using the Partial Least Squares (PLS) method. The results show that company size and leverage have positive and significant effects on the IFRS S1/S2 readiness score, whereas profitability has no significant effect. Simultaneously, company size, profitability, and leverage have a significant effect on readiness to implement IFRS S1/S2. These findings contribute to the development of sustainability reporting literature and strengthen the relevance of legitimacy theory and stakeholder theory in explaining corporate readiness for sustainability standards. The conclusion of the study emphasizes that corporate structural capacity and external pressure are important factors in supporting readiness to implement IFRS S1/S2 among LQ45 issuers.